2021
DOI: 10.3390/cimb43010011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Underlying Genistein Treatment of Wound Healing: A Review

Abstract: Estrogen deprivation is one of the major factors responsible for many age-related processes including poor wound healing in postmenopausal women. However, the reported side-effects of estrogen replacement therapy (ERT) have precluded broad clinical administration. Therefore, selective estrogen receptor modulators (SERMs) have been developed to overcome the detrimental side effects of ERT on breast and/or uterine tissues. The use of natural products isolated from plants (e.g., soy) may represent a promising sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…This phenomenon may be explained by the fact that when the fiber density and amount of drug rise, the likelihood of 3D cell multiplication also increases 39 . But, to understand the biological mechanisms following genistin therapy, it is essential to focus on the potential and innovative pharmacological interventions associated with phytoestrogen-induced wound healing 40 .
Figure 11 Cell viability of L929 cultured on nanofibers after 24 and 72 h; this test was performed with a significance level of P < 0.01 with ANOVA analysis.
…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…This phenomenon may be explained by the fact that when the fiber density and amount of drug rise, the likelihood of 3D cell multiplication also increases 39 . But, to understand the biological mechanisms following genistin therapy, it is essential to focus on the potential and innovative pharmacological interventions associated with phytoestrogen-induced wound healing 40 .
Figure 11 Cell viability of L929 cultured on nanofibers after 24 and 72 h; this test was performed with a significance level of P < 0.01 with ANOVA analysis.
…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In a previous study, we fabricated a soy protein and collagen hybrid protein scaffold and demonstrated that the scaffold supported the growth of hippocampal neurons, HMC3 cells and neural stem cells [ 24 ]. Other studies have suggested that soy protein may modulate the immune response in wounded tissue, because soy isoflavones regulate cytokine production and the function of immune cells [ 7 , 8 , 43 ]. However, it is not yet known how microglial cells respond to a scaffold containing soy protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many cytokines, including IL‐10 and IL‐6 and tumor necrosis factor‐ α (TNF‐α), uses tyrosine kinases in their signaling pathways (Dahle et al, 2004 ; Page et al, 2009 ). It has been shown that inhibition of tyrosine kinase by genistein reduces monocyte chemoattractant protein (MCP‐1) excretion via inhibition of TNF‐α‐induced NFκ B activation (Čoma et al, 2021 ; Kim, 2021 ). In this regard, genistein‐induced inhibition of tyrosine kinase exerts anti‐inflammatory effects which could be a potential mechanism for preventing SARS‐CoV‐2‐induced lung injury.…”
Section: Pharmacological Effects Of Genistein As a Probable Beneficia...mentioning
confidence: 99%